REPRESENTING VIETNAM’S POLITICAL LEADERSHIP IN INTERNATIONAL MEDIA: A CRITICAL DISCOURSE ANALYSIS OF COVERAGE FROM 2018 TO 2024 - Kumaat, Jackson Andre William (International Review of Humanities Studies, 2025)
International media play a powerful role in shaping global perceptions of political legitimacy, particularly in states where authoritarian governance coexists with economic success. Vietnam—often described as a one-party socialist state with rapid economic growth—has attracted increased attention in international news coverage, yet little research has examined how its leadership is discursively constructed through media narratives. This study addresses that gap by analyzing how Vietnam’s political leadership was represented in international media from 2018 to 2024. Using Norman Fairclough’s Critical Discourse Analysis (CDA) and Stuart Hall’s theory of representation, the research investigates how ideology, power, and meaning are embedded in news coverage from seven major outlets: BBC News, The Guardian, The Straits Times, Al Jazeera, Le Monde, Reuters, and the South China Morning Post. From a qualitative analysis of 40 purposively sampled articles, three dominant narratives emerge: (1) Vietnam’s leadership is portrayed as authoritarian, especially in relation to media control; (2) political reforms are framed as pragmatic and tied to economic performance; and (3) legitimacy is constructed through effective governance during crises. These findings reveal that representations of leadership are shaped not only by events in Vietnam, but also by the ideological positions and geopolitical interests of the media outlets themselves. This study contributes to political communication and media representation research by showing how leadership in socialist states is symbolically constructed and evaluated through transnational discourse.